Test particle energization of heavy ions in magnetohydrodynamic turbulence - Pugliese, Facundo Leonel (2022)
In the present work, we study the energization and displacement of heavy ions through the use of test particles interacting with the electromagnetic fields of magnetohydrodynamic (MHD) turbulence. These fields are obtained from pseudospectral direct numerical solutions of the compressible three-dimensional MHD equations with a strong background magnetic field. We find particle energization to be predominantly perpendicular as the ions become heavier (lower charge-to-mass ratio) and that high displacement is detrimental for perpendicular energization. On the other hand, perpendicular displacement is unaffected by the charge-to-mass ratio, which we explain with a simple guide center model. Using Voronoi tessellation along with this model, we analyze preferential concentration and find that particles behave as tracers in the perpendicular plane, clustering in regions with · u < 0. These regions also have (× E ) z < 0, which is optimal for perpendicular energization, thus providing a mechanism to understand precedent results.